Impact of Digital Payment System on the Efficiency of the Indian banking sector - Deepa Garg and Dr. Shalini Singh (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
This study investigates the impact of digital payment systems on the efficiency of the Indian banking sector. Utilizing a quantitative research design, data was collected from 300 banking institutions across major urban centers in India through structured questionnaires and secondary sources. Correlation and regression analyses were conducted to assess the relationship between Digital Payment Systems (DPS) and the Efficiency of the Indian Banking Sector (EIBS). Results indicate a strong positive correlation (0.67) between DPS and EIBS, with approximately 44.89% of the variance in banking efficiency explained by digital payments. The findings suggest that enhanced digital payment infrastructure significantly contributes to improved banking efficiency, emphasizing the need for ongoing investment in digital technologies and user education. This research highlights the importance of digital payment systems in promoting operational effectiveness and financial inclusion in India.